360° AUDIOVISUAL JOURNALISM: a study on user perceptions of sense of presence and credibility - Souza Lima, Luciellen; Oliveira Barbosa, Suzana (Brazilian journalism research, 2023)
ABSTRACT – The increasing use of high technology in journalism has led to new formats of content production. In this paper, we focus on one of these formats: 360° audiovisual reports. This format uses virtual reality (VR) and aims to produce a certain sense of presence in virtual environments. We seek to understand the relationship between this sense of presence and credibility, in addition to identifying which user perceptions may be linked to credibility. Our methodology involved developing a reception study which included experimental research, conducting interviews, and applying a questionnaire. The results point to a positive correlation between the variables, reinforcing relationships pointed at in other studies and demonstrating the importance of perceptions like freedom of choice, less manipulation/more transparency, and sensationalism. RESUMO – Em um contexto de crescente utilização de alta tecnologia no jornalismo, novos formatos têm sido incorporados à produção de conteúdo. Neste artigo, nossa atenção se volta para o estudo de um desses formatos: reportagens audiovisuais em 360°, que utilizam a realidade virtual (RV) e visam provocar algum nível de sensação de presença em ambientes virtuais. Buscamos entender a relação entre sensação de presença e credibilidade, além de identificar quais percepções dos usuários podem estar ligadas à credibilidade. Metodologicamente, desenvolvemos um estudo de recepção, envolvendo pesquisa experimental, realização de entrevistas e aplicação de questionário. Os resultados apontam uma correlação positiva entre as variáveis, reforçam relações apontadas em outras pesquisas e demonstram a importância de percepções como liberdade de escolha, menos manipulação/mais transparência e sensacionalismo. RESUMEN – En un contexto de creciente uso de alta tecnología en el periodismo, se han incorporado nuevos formatos a la producción de contenidos. En este artículo, nuestra atención se centra en el estudio de uno de estos formatos: los reportajes audiovisuales en 360°, que utilizan la realidad virtual (VR) y pretenden provocar algún nivel de sensación de presencia en entornos virtuales. Buscamos comprender la relación entre sensación de presencia y credibilidad, además de identificar qué percepciones de los usuarios pueden estar vinculadas a la credibilidad. Metodológicamente, se desarrolló un estudio de recepción, involucrando investigación experimental, realización de entrevistas y aplicación de un cuestionario. Los resultados apuntan a una correlación positiva entre las variables, refuerzan relaciones señaladas en otros estudios y demuestran la importancia de percepciones como libertad de elección, menos manipulación/más transparencia y sensacionalismo.